Назви художніх творів та заголовки як перекладацька проблема (на матеріалах англомовної художньої літератури в перекладах українською) - Воробйова, Тетяна; Смалько, Людмила; Vorobiova, Tetiana; Smalko, Liudmyla (Східноєвропейський національний університет імені Лесі Українки, 2018)
Предметом наукового дослідження у статті є креативні перекладацькі стратегії в перекладах назв художніх творів і заголовків. У центрі уваги взаємозв’язок таких аспектів, як креативність, свобода і правильність перекладу у процесі передачі конотативної і національно-культурної семантики заголовка. Детально проаналізовані сучасні наукові студії в галузі вітчизняного і зарубіжного перекладознавства. Дослідження здійснено на матеріалі англомовної художньої літератури в перекладах українською. The article highlights the problems of the creative approach to translation activities. In this study, translation is considered both as a process and as a product or result of the creative translation. The emphasis is laid on the contemporary research in the field of psycholinguistics and the theory of translation, which laid the foundations for the new approaches to the interpretation of the translation process, problems of free translation and creativity. The author substantiates the essence of key concepts and provisions concerning the research problem: creativity, creativity and freedom of translation, fidelity of translation, neologism, title of the book, concept of reproduction in translation. The subleties of free translation and translational creativity are considered on the examples of the translation peculiarities of the English authors’ book titles translated into Ukrainian and neologisms. It is proved that freedom in the choice of linguistic and stylistic means of the target language in translation contributes to the formation and development of translation creativity and helps a translator to achieve faithfulness in transferring concepts of the source language. The article suggests directions of further scientific research concerning the creativity of translation activities, including the degree of freedom and creativity in the translation of fantasy children’s literature, translation as a re-creative activity, plurality of translation as an implementation of the creative potential of the translator.
The Вook Titles as a Translation Problem (case study of the English Fiction Titles in the Ukrainian Translations)
Keywords: назва художнього твору; заголовок; креативний переклад; свобода перекладу; правильність і точність перекладу; creativity; creative translation; freedom in translation; author's neologisms; heading; title; faithfulness of translation